2020
DOI: 10.3390/cancers12010139
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PP2A with LB-100 Enhances Efficacy of CAR-T Cell Therapy Against Glioblastoma

Abstract: Chimeric antigen receptor (CAR)-engineered T cells represent a promising modality for treating glioblastoma. Recently, we demonstrated that CAR-T cells targeting carbonic anhydrase IX (CAIX), a protein involved in HIF-1a hypoxic signaling, is a promising CAR-T cell target in an intracranial murine glioblastoma model. Anti-CAIX CAR-T cell therapy is limited by its suboptimal activation within the tumor microenvironment. LB-100, a small molecular inhibitor of protein phosphatase 2A (PP2A), has been shown to enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…However, suppressing CAR T cell exhaustion by PTPN2 ablation might not always have desirable output, as for example deletion of the PTPN2encoding gene (Ptpn2) in CD8 T cells enhanced the ratio of terminally exhausted T cell populations (TIM-3 + T cells) to progenitor exhausted T cells (SLAMF6 + T cells) by increasing the number of TIM-3 + cells without depleting the pool of SLAMF6 + populations [66]. To disrupt PP2A function, Zhuang and colleagues used the small molecule LB-100, and found that inhibition of this phosphatase increased the therapeutic efficacy of CAR T cells [69].…”
Section: Ptpn2 and Pp2amentioning
confidence: 99%
“…However, suppressing CAR T cell exhaustion by PTPN2 ablation might not always have desirable output, as for example deletion of the PTPN2encoding gene (Ptpn2) in CD8 T cells enhanced the ratio of terminally exhausted T cell populations (TIM-3 + T cells) to progenitor exhausted T cells (SLAMF6 + T cells) by increasing the number of TIM-3 + cells without depleting the pool of SLAMF6 + populations [66]. To disrupt PP2A function, Zhuang and colleagues used the small molecule LB-100, and found that inhibition of this phosphatase increased the therapeutic efficacy of CAR T cells [69].…”
Section: Ptpn2 and Pp2amentioning
confidence: 99%
“…They reported that LB100 administration sensitized GBM cells to the cytotoxic effects of radiation in vitro and significantly delayed tumor growth in vivo after radiation (p<.001) [91]. Recently, another study reported combining LB100 and chimeric antigen receptor (CAR)-engineered T cells to treat GBM (Table 1) [92].…”
Section: Glioblastomamentioning
confidence: 99%
“…(CAIX), a protein involved in hypoxic signaling, and LB100 in GBM cell lines [92]. Combination therapy in vitro demonstrated a synergistic effect of LB100 and CAR-T cells and a significant increase in cytotoxic markers.…”
Section: Cui Et Al Initially Tested the Combination Of Car-engineered T Cells Targeting Carbonic Anhydrase IXmentioning
confidence: 99%
“…Thus, small molecule inhibitors of PP2A such as LB-100 [105], are emerging as novel strategies for SCLC. Furthermore, since PP2A is also associated with immune response by downregulating cytotoxic T-lymphocyte function [106,107], PP2A inhibition combined with immunotherapy appears to be effective in mediating an antitumor response. Indeed, in colon cancer and melanoma cells, a combination of LB-100 and an immune checkpoint inhibitor led to greater T-cell-dependent anti-tumor response, with more effector T-cell and reduced regulatory T-cell infiltration [106].…”
Section: Protein Phosphatase 2a (Pp2a)mentioning
confidence: 99%